#TITLE_ALTERNATIVE# - SAPUTRA (NIM : 10108109) ; Pembimbing : Dr. Muchtadi Intan Detiena, MARIO
In 2005, National Security Agency in United States (NSA) recommends the use of Elliptic Curve Cryptography (ECC) as the basis for all cryptographic algorithms. ECC is very efficient because it needs smaller key than other cryptosystems for the same security level. The security of ECC depends on how to solve Elliptic Curve Discrete Logarithm Problem (ECDLP). And the best algorithm to solve the ECDLP is Pollard Rho. Even so, the original Pollard Rho Algorithm is still not efficient enough. Pollard Rho uses iteration function to produce a random walk. But to make the algorithm more efficent, the iteration function should produce random random walk. In this work, we will explain Pollard Rho Algorithm and its modification on Elliptic Curve Cryptography.